Higher UHMWPE wear-rate in cementless compared with cemented cups with the Saturne® Dual-Mobility acetabular system. Issue 2 (March 2018) - Tabori-Jensen, Steffan; Frølich, Christina; Hansen, Torben B.; Bøvling, Søren; Homilius, Morten; Stilling, Maiken
Introduction: Dual mobility (DM) total hip arthroplasty (THA) may reduce dislocation risk, but might increase the risk of high polyethylene (PE) wear due to double wearing surfaces. Methods: 127 patients (97 female) with 129 hips operated with THA after displaced femoral neck fracture FNF between 2005 and 2011, were seen for a cross-sectional clinical follow-up. Acetabular components were Saturne® DM cups with 28mm chrome-cobalt heads in UHMWPE. Cementless cups (n = 73) were hydroxyapatite coated. Radiographs were obtained for analysis of cup placement, 2D polyethylene wear and wear-rate (PolyWare 3D), and further radiological evaluation. Activity measurements included Timed Up and Go test (TUG) and walking distance from Harris Hip Score (HHS). Results: At a mean follow-up of 2.83 (1.0-7.7) years the mean wear was 0.82 mm (range 0.17-4.51, SD 0.50), and the wear-rate was 0.37 mm (range 0.06-1.90, SD 0.29). Wear-rate of 0.43 mm/year (SD 0.30) in cementless cups was higher (p = 0.004) than 0.30 mm/year (SD 0.27) in cemented cups. Mean age at time of surgery was 75.1 years (range 30-95). There was no correlation between age at time of surgery and wear (p = 0.56). There was no correlation between cup inclination and wear-rate (p = 0.35). TUG was mean 13.4 seconds (range 4.5-30.1) and correlated with wear rate (p = 0.03). Conclusions: At short term follow-up, the mean wear-rate in old and low demand patients was high, correlated to activity, and was above the generally accepted osteolysis threshold (0.1 mm/yr.). Cementless HA-coated cups had higher wear-rate than cemented cups.